Magnifying Endoscopy for Esophageal Ectopic Sebaceous Glands - Jeon, Mu Song (Clin Endosc, 2018)
Ectopic sebaceous glands are found very rarely in the esophagus; heretofore, several cases have been reported. The sebaceous gland is originally a source of an endodermal origin; however, there have been controversies regarding whether the origin of the esophageal ectopic sebaceous gland is ectodermal or endodermal. Ectopic sebaceous glands of the esophagus usually do not cause symptoms; thus, they are often found incidentally on endoscopy for routine health screening. Endoscopic findings are characterized by single or multiple yellow patches or nodular lesions of various sizes, sometimes with small central openings. We report two cases of esophageal ectopic sebaceous glands found incidentally during endoscopy with magnifying endoscopic findings. The lesions were in the mid-esophagus and lower esophagus, respectively, and both endoscopic findings were similar as multiple yellowish patches or plaques. Magnifying endoscopy revealed the openings of the excretory ducts surrounded by circular microvessels in both cases.